An integrated approach to the diagnosis, treatment and prevention of caries in early and preschool age children - Daniil A. Simonenko; Veronika A. Zhurbenko; Anastasiya E. Karlash (RUDN Journal of Medicine, 2024)
Relevance. Dental caries, according to World Health Organization, is one of the most common diseases in children throughout the world. In the absence of timely diagnosis and treatment, the carious process can affect not only the efficiency of chewing function, but also speech, smile and, as a consequence, psychosocial adaptation, as well as the quality of life of the child and family. Despite the fact that the etiological factors have been well known for many years, reducing the number of teeth affected by caries in children still remains an urgent task. This article is a review of information sources about the prevalence, etiology and integrated approach to the diagnosis, treatment and prevention of dental caries in children. The authors analyzed scientific data in the search engines PubMed, Google Scholar and eLibrary. Conclusion . Based on the literature review, a number of modern trends were identified that define a series of key hypotheses that summarize the accumulated material and confirm the prospects and relevance of the problem. The goal is to help clinicians recognize common patterns of caries in children and make appropriate decisions regarding the diagnosis, treatment and prevention of carious lesions, taking into account available methods, materials, knowledge, age and patient history. It is also important to create a comfortable and safe environment during the appointment, as unfamiliarity with a new physical interaction can provoke anxiety as a standard response to uncertainty, which often results in childhood dental phobia, contributing to behavioral resistance to return visits. In general, based on the analysis, we can conclude that the use of an integrated approach to diagnosis and treatment has great potential for achieving better results in working with dental patients of early and preschool age, the development and improvement of which should remain a priority to ensure more complete and effective treatment of children and maintaining their health in the long term.